Aluminum-iron-manganese master alloy and preparation method thereof
By designing a ternary intermediate alloy of aluminum and ferromanganese, the phase structure and casting conditions are controlled, and the problems of Fe and Mn elements in high-strength brass smelting are solved, and the components of the alloy are difficult to regulate, so that small composition segregation, reasonable phase composition, and smelting are achieved. The effect of high metal yield.
Patent Information
- Application Number
- CN202310195236.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The prior art is difficult to effectively solve the problems of difficult addition of Fe and Mn elements in high-strength brass smelting, resulting in unreasonable component segregation, unreasonable phase composition, and low yield of smelted metals.
Design a ternary intermediate alloy of ferromanganese aluminum, with mass percentage compositions of Fe: 20-30 wt%, Mn: 20-30 wt%, Cu: 3-7 wt%, Mg: 0.003-0.05 wt%, and the balance is Al and non-existent Avoid impurities. By controlling the casting temperature and the cooling rate of the ingot, a reasonable phase structure is formed, including the Al3Fe phase, the primary Al3FeMn phase and the secondary Al3FeMn phase. The area of the primary Al3FeMn phase accounts for ≥60%, and the area of the Al3Fe phase accounts for 20-38 %, the area of the secondary Al3FeMn phase accounts for less than 5%.
Aluminum and manganese intermediate alloy with small composition segregation, reasonable phase composition and high yield of smelting metals is realized, with metal yield of more than 90%, which solves the difficulty of adding Fe and Mn elements in high-strength brass smelting. Issues of regulation.
Smart Images

Figure CN116162828B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper alloys, and in particular relates to an aluminum-iron-manganese master alloy and a preparation method thereof. Background Art
[0002] Master alloys are composed of two or three components, one or two of which are refractory or easily burned. They are transition alloys. The purpose of using master alloys in copper alloy smelting is to facilitate the addition of alloy elements with high melting points or easily oxidized and burned, shorten the smelting time, reduce metal burning, and obtain copper alloys with uniform and accurate composition.
[0003] High-strength brass is a complex brass alloy composed of five main elements: Cu, Zn, Al, Fe, and Mn. It has excellent wear resistance and is used to manufacture various key wear-resistant parts of engineering machinery. The European standard number is CuZn25Al6Fe3Mn3, and the American standard number is C86300. The chemical composition of the alloy is Cu: 60-65wt%, Mn: 2.5-5.0wt%, Al: 5.0-7.5wt%, Fe: 2.0-4.0wt%, Sn≤0.2wt%, Ni≤0.5wt%, Pb≤0.2wt%, Si≤0.1wt%, and the balance is Zn.
[0004] The smelting of high-strength brass usually uses red copper, zinc, aluminum, iron, manganese and a certain proportion of high-strength brass scraps as raw materials. Since the melting point of Fe is as high as 1538℃, the melting point of Mn is also 1244℃, and the melting point of brass is generally 900-1000℃, the smelting temperature is usually around 1000℃. If pure iron and pure manganese are directly added during smelting, the smelting temperature needs to be increased, and it takes a long time to completely melt. In addition, due to the complex elements of high-strength brass, it is difficult to control the chemical composition of the alloy. If the method of adding Cu-Fe and Cu-Mn master alloys is adopted, although the problem of difficult melting of iron and manganese can be solved, due to the high content of Fe and Mn in high-strength brass, a large amount of Cu-Fe and Cu-Mn master alloys need to be added, which increases the cost of raw materials, and the temperature of Cu-Fe master alloy still reaches above 1200℃, and it is not easy to melt quickly in brass; in addition, when Al is directly added to brass, a large amount of heat will be released, causing local overheating of the melt and affecting the quality of the melt.
[0005] If the three metals Al, Fe and Mn in high-strength brass are prepared in advance in a certain ratio into a ternary master alloy for high-strength brass smelting, not only can the melting speed be greatly accelerated and the smelting time be shortened, but also because the three components have been matched in proportion, it is easier to obtain a more accurate alloy composition. However, the composition segregation, phase composition and molten metal yield of the ternary master alloy are difficult points in process control, and therefore, further improvement is needed. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide an aluminum-iron-manganese intermediate alloy with small component segregation, reasonable phase composition and high smelting metal yield.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing an aluminum-iron-manganese master alloy.
[0008] The technical solution adopted by the present invention to solve the first technical problem is: an aluminum-iron-manganese master alloy, characterized in that the mass percentage composition of the aluminum-iron-manganese master alloy is Fe: 20-30wt%, Mn: 20-30wt%, Cu: 3-7wt%, Mg: 0.003-0.05wt%, and the balance is Al and inevitable impurity elements.
[0009] Fe: The solid solubility of Fe in Al is very low. Once its content exceeds the solid solubility limit, it will first form Al3Fe brittle phase with Al, increasing the brittleness of the alloy. When the Fe content exceeds 30wt%, the Fe component segregation is more serious, and the proportion of Al3Fe in the ternary alloy phase will increase, exceeding the upper limit controlled by the present invention.
[0010] Mn: Mn forms brittle Al3FeMn compound with Al and Fe. Al3FeMn is the product of Mn solid solution in Al3Fe replacing part of Fe. When the Mn content is lower than 20wt%, the Al3FeMn phase ratio will decrease, and when it is added to high-strength brass as an intermediate alloy, the Mn content will not meet the standard, and additional Mn needs to be added; when the Mn content is higher than 30wt%, although it can promote the formation of Al3FeMn phase, when it is added to high-strength brass as an intermediate alloy, the Mn content will exceed the standard.
[0011] Cu: Cu reduces the melting rate of Fe. Cu is easier to melt into liquid than Fe. When solid Fe is immersed in liquid copper, it begins to dissolve through the diffusion of Fe atoms, which accelerates the melting rate of iron sheets. When the Cu content is lower than 3wt%, when smelting aluminum-iron-manganese master alloy, the amount of electrolytic copper added is too small, and the liquid copper water after melting is not enough to dissolve the iron sheet; when the Cu content exceeds 7wt%, the content of the main components Al, Fe, and Mn in the master alloy will be reduced.
[0012] Mg: Mg plays two main roles in the alloy of the present invention: first, Mg can react with H in the melt to generate MgH, which plays a role in degassing and eliminates pores in the aluminum-iron-manganese master alloy; second, the solid solubility of Mg in the matrix is very low, but the solid solubility in the Al3Fe phase is relatively high, reaching 3%, so Mg is solid-dissolved in the primary Al3FeMn phase, occupies a favorable position at the solid-liquid interface, hinders the diffusion of Fe atoms, inhibits the growth of point-like Al3FeMn phases, and avoids the formation of coarse fishbone-like Al3FeMn phases. When the Mg content is less than 0.003wt%, the effect of Mg on inhibiting the growth of point-like Al3FeMn phases is very weak, and when the Mg content exceeds 0.05wt%, the diffusion of Fe atoms is hindered, and the segregation of Fe in the master alloy is aggravated.
[0013] Preferably, the phase structure of the aluminum-iron-manganese intermediate alloy includes Al3Fe phase, primary Al3FeMn phase and secondary Al3FeMn, wherein the area proportion of the primary Al3FeMn phase is more than 60%, the area proportion of the Al3Fe phase is 20-38%, and the area proportion of the secondary Al3FeMn phase is less than 5%.
[0014] Al3Fe phase is the main component phase of aluminum-iron-manganese intermediate alloy, which is a binary composition of Al and Fe. The higher its proportion is, the more serious the segregation of Mn element is. However, if its proportion is too small, the proportion of secondary Al3FeMn phase will increase. Therefore, in the alloy structure of the present invention, the area proportion of Al3Fe phase is controlled at 20-38%.
[0015] The primary Al3FeMn phase is a matrix phase, which is a compound formed by three elements of Al, Fe and Mn. The larger its proportion in the master alloy structure is, the more reasonable the composition ratio of the ternary master alloy is, and the smaller the segregation of Fe and Mn elements in the smelted high-strength brass alloy component is. In the alloy structure of the present invention, the area proportion of Al3FeMn is ≥60%.
[0016] Although the secondary Al3FeMn phase has the same chemical composition as the primary Al3FeMn phase, the crystal structure and morphology are different. The secondary Al3FeMn phase often appears in the aluminum-iron-manganese alloy in the form of fishbone and granular morphology. The secondary Al3FeMn phase is very stable at high temperatures. When smelting, it is added to the high-strength brass alloy as an intermediate alloy. The secondary Al3FeMn phase will be retained in the high-strength brass alloy structure, which will reduce the mechanical properties of the high-strength brass. At the same time, it is a hard particle, which will accelerate the wear of the tool during material processing. Therefore, in the alloy structure of the present invention, the area of the secondary Al3FeMn phase accounts for less than 5%.
[0017] Preferably, the secondary Al3FeMn phase is in a granular or fishbone shape, wherein the average size of the granular secondary Al3FeMn phase is ≤3μm, the average size of the fishbone-shaped Al3FeMn phase is ≤10μm, and the area ratio is ≤0.1%. The larger the size of the secondary Al3FeMn phase, the greater the negative impact, wherein the negative impact of the fishbone-shaped Al3FeMn phase is the most significant, so in the aluminum-iron-manganese master alloy of the present invention, the secondary Al3FeMn phase morphology needs to be controlled to be fine granular, with an average size of ≤3μm, and the average size of the fishbone-shaped secondary Al3FeMn phase is ≤10μm, and the area ratio is ≤0.1%. The secondary Al3FeMn phase is relatively stable at high temperatures. When it is distributed in the master alloy matrix in a fine granular shape, it is beneficial to the diffusion and dissolution of Fe and Mn during high-strength brass smelting, reducing element segregation and improving the uniformity of the composition.
[0018] Preferably, the Al3Fe phase is in block shape with an average size of ≤50 μm. Block and strip shape, block shape can reduce the segregation of Mn and improve the uniformity of alloy element distribution compared with strip shape, therefore, the morphology of Al3Fe phase in the alloy of the present invention should be controlled to be block shape.
[0019] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing an aluminum-iron-manganese master alloy, characterized in that it comprises the following preparation steps:
[0020] 1) Melting: Prepare the ingredients according to the required ingredients, and the melting temperature is 1100-1300℃;
[0021] 2) Casting: The casting temperature range is 1100-1200°C, and the ingot cooling rate is 400-600°C / s.
[0022] Casting temperature and solidification rate are important parameters for controlling the quality of master alloys. Master alloys with different microstructures can be obtained by using different casting temperatures and solidification rates. Under low casting temperatures and rapid solidification conditions, the growth of Al3Fe phase is inhibited. Blocky Al3Fe phase is formed under low-temperature casting of 940-1060℃ and rapid solidification conditions, while long strips of Al3Fe phase are easily formed under casting above 1200℃ and slow solidification conditions below 400℃ / s, and Al3FeMn phase needs to be formed under high-temperature casting above 1100℃ and rapid solidification conditions. Therefore, by controlling the casting temperature and the cooling rate of the ingot, the area of the primary Al3FeMn phase is controlled to account for more than 60%, while the Al3Fe phase is controlled to be blocky, and the segregation of the Fe element density is avoided, and the desired microstructure morphology can be obtained.
[0023] Preferably, in step 1), the order of adding materials is: electrolytic copper → iron sheet → electrolytic manganese → aluminum ingot, wherein the iron sheet is mixed with cryolite and added, and the amount of cryolite added is 0.5-2% of the total mass of the iron sheet; the electrolytic manganese is mixed with cryolite and added, and the amount of cryolite added is 0.5-2% of the total mass of the electrolytic manganese. Cryolite acts as a flux, which can form a solid phase low melting point mixture with Fe and Mn oxides to accelerate the melting of the iron sheet and electrolytic manganese, otherwise a large amount of metal oxides are easily generated when the iron sheet and electrolytic manganese are melted, floating on the surface of the melt to become oxide slag and cannot be melted into the liquid melt, reducing the metal recovery rate.
[0024] Preferably, in step 1), after the composition is tested and qualified, 0.02-0.08 wt% Zr of the melt mass is added to the smelting furnace, and then flake graphite is used for covering, and the covering thickness is not less than 80 mm. Zr is deoxidized, and the function of flake graphite covering is to isolate Zr from combining with oxygen in the air and burning.
[0025] Compared with the prior art, the invention has the following advantages: according to the requirements of the contents of the three elements Al, Fe and Mn of high-strength brass, the invention designs an aluminum-iron-manganese ternary master alloy, can reasonably control the morphology, size and distribution ratio of the master alloy phase, obtain the aluminum-iron-manganese master alloy with small component segregation, reasonable phase composition and high smelting metal yield, the metal yield is above 90%, and solves the problems of the current high-strength brass smelting that the Fe and Mn elements are not easy to add and the alloy composition is difficult to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a metallographic structure photograph of Example 1 of the present invention.
[0027] Figure 2 This is a metallographic structure photograph of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below with reference to the accompanying drawings.
[0029] The present invention provides 3 embodiments and 2 comparative examples, and the specific components are shown in Table 1.
[0030] The preparation steps of Example 1 are as follows:
[0031] 1) Melting: Melting is carried out in a 200kg medium frequency induction furnace at a melting temperature of 1100-1250°C. The raw materials added are as follows: iron sheet: 25kg, electrolytic manganese: 25kg, electrolytic copper: 5kg, aluminum ingot: 45kg, CuMg50 alloy: 0.37kg, and the order of adding materials is: electrolytic copper→iron sheet→electrolytic manganese→aluminum ingot, wherein the iron sheet is mixed with cryolite and added, and the amount of cryolite added is 0.8% of the total mass of the iron sheet; the electrolytic manganese is mixed with cryolite and added, and the amount of cryolite added is 0.8% of the total mass of the electrolytic manganese. After all the raw materials are melted, samples are taken for chemical composition analysis. After the composition is qualified, 0.085kg of Zr is first added to the smelting furnace for deoxidation, and then covered with baked red flake graphite with a covering thickness of 60mm, and then 0.37kg of CuMg50 alloy is added and fully stirred.
[0032] 2) Casting: The casting temperature is 1140-1160℃, and the melt is directly cast into a circulating cooling water tank with a cooling rate of 480℃ / s.
[0033] 3) Inspection.
[0034] The preparation steps of Example 2 are as follows:
[0035] 1) Melting: Melting is carried out in a 350kg medium frequency induction furnace at a melting temperature of 1140-1260°C. The raw materials added are as follows: iron sheet: 45kg, electrolytic manganese: 57kg, electrolytic copper: 8kg, aluminum ingot: 90kg, CuMg50 alloy: 2kg. The order of adding materials is: electrolytic copper→iron sheet→electrolytic manganese→aluminum ingot. Among them, the iron sheet is mixed with cryolite and added, and the amount of cryolite added is 1% of the total mass of the iron sheet; the electrolytic manganese is mixed with cryolite and added, and the amount of cryolite added is 1% of the total mass of the electrolytic manganese. After all the raw materials are melted, samples are taken for chemical composition analysis. After the composition is qualified, 0.18kg of Zr is first added to the smelting furnace for deoxidation, and then covered with baked red flake graphite with a covering thickness of 130mm, and then 2kg of CuMg50 alloy is added and fully stirred.
[0036] 2) Casting: The casting temperature is 1120-1150℃, and the melt is directly cast into a circulating cooling water tank with a cooling rate of 540℃ / s.
[0037] 3) Inspection.
[0038] The preparation steps of Example 3 are as follows:
[0039] 1) Melting: Melting is carried out in a 100kg medium frequency induction furnace at a melting temperature of 1160-1280°C. The raw materials added are as follows: iron sheet: 14kg, electrolytic manganese: 12kg, electrolytic copper: 3.5kg, aluminum ingot: 20.5kg, CuMg50 alloy: 0.6kg, and the order of adding materials is: electrolytic copper→iron sheet→electrolytic manganese→aluminum ingot, wherein the iron sheet is mixed with cryolite and added in an amount of cryolite of 1.5% of the total mass of the iron sheet; the electrolytic manganese is mixed with cryolite and added in an amount of cryolite of 1.5% of the total mass of the electrolytic manganese. After all the raw materials are melted, samples are taken for chemical composition analysis. After the composition is qualified, 0.06kg of Zr is first added to the smelting furnace for deoxidation, and then covered with baked red flake graphite with a covering thickness of 90mm, and then 0.6kg of CuMg50 alloy is added and fully stirred.
[0040] 2) Casting: The casting temperature is 1160-1180℃, and the melt is directly cast into a circulating cooling water tank with a cooling rate of 570℃ / s.
[0041] 3) Inspection.
[0042] The preparation process of Comparative Example 1 is the same as that of Example 1.
[0043] The difference between Comparative Example 2 and Example 1 is that the casting temperature is 1390-1430°C.
[0044] The following tests were performed on the microstructures of the obtained embodiments and comparative examples, and the results are recorded in Table 2; the metal yields and element segregation of the obtained embodiments and comparative examples were tested, and the results are recorded in Table 3.
[0045] Microstructure: The size and area ratio of the phases are analyzed using software under a metallographic microscope.
[0046] Metal yield: the ratio of the mass of the intermediate alloy ingot to the total mass of the input raw materials.
[0047] Element segregation: A manual drill was used to drill chips from 10 different parts of the aluminum-iron-manganese ingot, and the contents of three main alloying elements, Al, Fe and Mn, in the chips were analyzed using an inductively coupled plasma spectrometer. Among the 10 test results, the difference between the minimum and maximum element contents reflected the degree of element segregation. The smaller the difference, the smaller the degree of segregation of the element in the alloy.
[0048] Table 1 Composition / wt% of the Examples and Comparative Examples of the present invention
[0049]
[0050] Table 2 Microstructure of the embodiments of the present invention and the comparative examples
[0051]
[0052] Table 3 Metal yield and main alloy element segregation in the examples of the present invention and comparative examples
[0053]
Claims
1. An aluminum-iron-manganese master alloy, characterized in that: The aluminum-iron-manganese master alloy has a mass percentage composition of Fe: 20-30wt%, Mn: 20-30wt%, Cu: 3-7wt%, Mg: 0.003-0.05wt%, and the remainder is Al and unavoidable impurity elements; The phase structure of the aluminum-iron-manganese master alloy includes an Al3Fe phase, a primary Al3FeMn phase and a secondary Al3FeMn phase, wherein the area proportion of the primary Al3FeMn phase is more than 60%, the area proportion of the Al3Fe phase is 20-38%, and the area proportion of the secondary Al3FeMn phase is less than 5%; The secondary Al3FeMn phase is granular or fishbone-shaped, wherein the average size of the granular secondary Al3FeMn phase is ≤3μm, the average size of the fishbone-shaped Al3FeMn phase is ≤10μm, and the area ratio is ≤0.1%; The Al3Fe phase is in block form, with an average size of ≤50 μm.
2. A method for preparing the aluminum-iron-manganese master alloy according to claim 1, characterized in that: The method comprises the following preparation steps: 1) Melting: Prepare the ingredients according to the required ingredients, and the melting temperature is 1100-1300℃; 2) Casting: The casting temperature range is 1100-1200℃, and the ingot cooling rate is 400-600℃ / s.
3. The method for preparing the aluminum-iron-manganese master alloy according to claim 2, characterized in that: In the step 1), the order of adding materials is: electrolytic copper→iron sheet→electrolytic manganese→aluminum ingot, wherein the iron sheet is mixed with cryolite and the amount of cryolite added is 0.5-2% of the total mass of the iron sheet; the electrolytic manganese is mixed with cryolite and the amount of cryolite added is 0.5-2% of the total mass of the electrolytic manganese.
4. The method for preparing the aluminum-iron-manganese master alloy according to claim 2, characterized in that: In the step 1), after the components are tested and found to be qualified, 0.02-0.08 wt% of Zr based on the mass of the melt is added to the smelting furnace, and then flake graphite is used for covering, and the covering thickness is not less than 80 mm.
Citation Information
Patent Citations
Multivariate interalloy and smelting method thereof
CN101545061A
Low-carbon micro-calcium aluminum-manganese-iron alloy
CN104651702A